Effects of 1-methylcyclopropene on texture properties of Rabbiteye blueberry during long-term storage and simulated transportation - XIE,Guofang (2018)
Abstract In this work, the effects of 1-methylcyclopropene (1-MCP) on texture properties, titratable acidity (TA) and total soluble solids (TSS) in blueberry were examined during long term storage and simulated transportation. Blueberry fruits were stored at 0 ± 0.5 °C after being treated with 0.1, 0.2 and 0.3μL L-11-MCP. After 40 and 80 days of storage, quickly put 8 punnets into a foam box with commercial cold pack to simulate the commercial transportation for 2 days at 25 °C. There were considerable differences in the texture properties during long term storage and simulated transportation with 1-MCP. The 0.3 μL L-1 1-MCP can effectively decreased the decline of gumminess and chewiness, retarded the reduction of TA, and delayed blueberry fruit softening. There was significant positive correlation among firmness, springiness, cohesiveness, gumminess, chewiness, resilience, TSS, and TA. These results demonstrate that the 0.3 μL L-1 1-MCP combines with commercial polyethylene bags were successful effect in maintaining the texture properties of blueberry.